Improvement of Biorefinery Efficiency for Microalgae Nannochloropsis sp. via Harvesting Technology Evaluation (2018)
Recently, microalgal biomass has attached much attention due to the wide diversity of compounds synthesized from different metabolic pathways. This work attempts to study metabolites recovery from Nannochloropsis sp. biomass concentrated by centrifugation and flocculation. Carbohydrates were obtained using acid and alkaline hydrolysis required for cell disruption. Protein extraction was performed after alkaline pretreatment and lipids were recovery by acid hydrolysis- Soxhlet and alkaline hydrolysis- Soxhlet extraction routes. It was found that carbohydrates were recovered by acid hydrolysis in 41 % and 35.39 % for centrifuged and flocculated biomass, respectively, values higher than thus reported using alkaline hydrolysis. For protein extraction, centrifuged biomass exhibited higher recovery yield (55.48%) than flocculated biomass (38.40%). The lipid extraction route that achieved highest yield (43.45%) was acid hydrolysis with HCl followed by Soxhlet extraction with hexane. In addition, statistical analysis by T test suggested that flocculants affect negatively biomass culture, hence, efficiency of metabolites extraction.